(3QaY GdCTcGd aj eSGMI GdCTcGds - (3CHj YHO Gddg jYjT Hf EHQGgje Hf jhSa Hf SeGc, GdCehj GdGfOdS,J (B900 (3g` s ((3CMeO Hf Ydi GdUfgGLi s)
(3ChdgG (B:s
(3bGd GdTjN jYjT Hf GHQGgje GdeSGMI JLRFI GdTF GdeLghd HTF eYdhe s
(3BNQgG (B:s
(3hSHYI eLSeI JbOegG UaI GdRhGjG GdKdGKI hGdMeO ddg Ydi eG CLRd ef LRjd YWGFg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JUMjMGJ deGdcgG GdTjN YHO Gddg GdEHQGgje ef Cgd HQjOI GdCfHgG CTcGd gfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN YHO Gddg GdEHQGgje Bd Sdje GdNGUI HHQjOIs
Keywords: (3GdQjGVjGJs